Assessing transactive memory system and team performance: the moderating role of leadership efficacy. (3rd April 2022) - Lin, Chieh-Peng; Liu, Chu-Mei; Hsiao, Chuan-Yu
Abstract : Drawing upon transactive memory theory and social cognitive theory, this study establishes a research model that evaluates team performance from the mediating aspect of a transactive memory system (TMS), which is hypothetically influenced by social interaction, politics and learning goal orientation. Leadership efficacy is examined as a moderator in the development of the TMS. The empirical examinations of this study were tested using the data of high-tech teams from a large industry zone in Taiwan. Finally, this study discusses practical implications, research implications, and limitations based on its empirical results.